SOSIALISASI PEMBUATAN PUPUK ORGANIK UNTUK JERUK SIAM JESIGO DI NAGARI KOTO TINGGI KECAMATAN GUNUNG OMEH KABUPATEN LIMA PULUH KOTA - Weriantoni Weriantoni; Fitria Dita Rahmatina (BULETIN ILMIAH NAGARI MEMBANGUN, 2023)
Gunung Omeh Sub-District is renowned for its production of Jesigo oranges. With an area spanning 156.54 km², one of the areas within Gunung Omeh Sub-District known for Jesigo orange cultivation is Nagari Koto Tinggi. As one of the largest Jesigo orange-producing regions in West Sumatra, it is essential to empower citrus farmers in Nagari Koto Tinggi to realize the Nagari Organik program through the socialization of organic fertilizer use in citrus farming to enhance soil's physical, chemical, and biological properties. The objective of this initiative is to boost Jesigo orange production in Gunung Omeh Sub-District, particularly in Nagari Koto Tinggi, thereby increasing the income of citrus farmers. The method employed involves socialization and practical training related to organic fertilizer production. The findings from this initiative reveal that the community in Nagari Koto Tinggi had not been using organic fertilizer, even though farmers can produce it themselves. Citrus farming land is also provided with organic fertilizer due to a lack of knowledge and information regarding organic fertilizer production. Following participation in this program, the participants' knowledge and skills concerning the creation, benefits, and advantages of organic fertilizer have significantly improved. The aim is for the community to start producing organic fertilizer that can be directly applied to farmland, reducing the reliance on chemical fertilizers and pesticides. This shift is expected to decrease dependence on chemical fertilizers and pesticides, which have negative environmental and health impacts. Furthermore, it is anticipated that the people of Nagari Koto Tinggi will establish a cooperative dedicated to agriculture.